2015
DOI: 10.1186/s12885-015-1032-4
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates the TLR4-mediated inflammatory response through MyD88- and TRIF-dependent signaling pathways in an in vivo model of ovarian cancer

Abstract: BackgroundToll-like receptors (TLRs) are effector molecules expressed on the surface of ovarian cancer (OC) cells, but the functions of the TLR2/TLR4 signaling pathways in these cells remain unclear. Melatonin (mel) acts as an anti-inflammatory factor and has been reported to modulate TLRs in some aggressive tumor cell types. Therefore, we investigated OC and the effect of long-term mel therapy on the signaling pathways mediated by TLR2 and TLR4 via myeloid differentiation factor 88 (MyD88) and toll-like recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 51 publications
(67 reference statements)
3
74
0
1
Order By: Relevance
“…Melatonin is recognized as a novel potential modulator of MSCs differentiation and has been proven to be able to potently promote osteogenesis and osteoblast maturation through several pathways, including MAPK signaling, Wnt/beta‐catenin signaling, and BMP‐SMAD1 signaling . On the other hand, melatonin has also been found to exert anti‐inflammatory actions by downregulating pro‐inflammatory cytokines, scavenging oxygen free radicals, reducing nitric oxide production, and blunting NLRP3 (nucleotide‐binding domain, leucine‐rich repeat containing receptor‐related protein 3) inflammasome activation . Melatonin was shown to be able to suppress TNFα signaling activation in numerous different inflammatory models and also directly decrease TNFα production via several mechanisms, such as PI3K/Akt signaling activation, NF‐κB signaling inhibition, and the scavenging of reactive oxygen species .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is recognized as a novel potential modulator of MSCs differentiation and has been proven to be able to potently promote osteogenesis and osteoblast maturation through several pathways, including MAPK signaling, Wnt/beta‐catenin signaling, and BMP‐SMAD1 signaling . On the other hand, melatonin has also been found to exert anti‐inflammatory actions by downregulating pro‐inflammatory cytokines, scavenging oxygen free radicals, reducing nitric oxide production, and blunting NLRP3 (nucleotide‐binding domain, leucine‐rich repeat containing receptor‐related protein 3) inflammasome activation . Melatonin was shown to be able to suppress TNFα signaling activation in numerous different inflammatory models and also directly decrease TNFα production via several mechanisms, such as PI3K/Akt signaling activation, NF‐κB signaling inhibition, and the scavenging of reactive oxygen species .…”
Section: Discussionmentioning
confidence: 99%
“…In this model, melatonin reduced the frequency of ovarian carcinomas, sarcomas and cystic teratomas, diagnosed on the basis of histological subtype [229]. Subsequent studies confirmed that the molecular events normally associated with this type of experimental ovarian cancers were reversed by melatonin treatment [230,231,232]. Most recently, quantitative profiling of these tumors verified the broad modulatory actions of melatonin on essential signaling pathways in ovarian cancer cells [233] hinting at the possibility that melatonin should be considered as a therapeutic opportunity for women with this deadly disease.…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 98%
“…Toll-like receptors activation, via a myeloid differentiation primary response gene 88 (MyD88)-dependent pathway, induces an inflammatory response and promotes activation of the transcription factor NF-κB. The antiproliferative effect of melatonin involves negative regulation of MyD88 [33] and NF-κB [34]. These factors have proliferative effects by direct action on cyclin D1.…”
Section: Inactivation Of Nuclear Factor Kappa-light-chain-enhancer Ofmentioning
confidence: 99%